2016
DOI: 10.1111/jcmm.12923
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from mature dendritic cells increase endothelial inflammation and atherosclerosis via membrane TNF‐α mediated NF‐κB pathway

Abstract: Whether dendritic cell (DC) derived exosomes play a role in the progression of endothelial inflammation and atherosclerosis remains unclear. Using a transwell system and exosome release inhibitor GW4869, we demonstrated that mature DCs contributed to endothelial inflammation and exosomes were involved in the process. To further confirm this finding, we isolated exosomes from bone marrow dendritic cell (BMDC) culture medium (named DC‐exos) and stimulated human umbilical vein endothelial cell (HUVEC) with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(167 citation statements)
references
References 31 publications
3
155
0
1
Order By: Relevance
“…Thus, IκBα levels increased by miR‐16 sequestered more NF‐κB proteins in the cytoplasm and alleviated the activity of the signaling pathway. It was reported that the exosomes derived from mature DCs increased endothelial inflammation and atherosclerosis via the membrane TNFα‐mediated NF‐κB signaling pathway . It is feasible that the different results are due to the discrepancy of the packaged contents between exosomes derived from DCs and LIPUS‐treated DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IκBα levels increased by miR‐16 sequestered more NF‐κB proteins in the cytoplasm and alleviated the activity of the signaling pathway. It was reported that the exosomes derived from mature DCs increased endothelial inflammation and atherosclerosis via the membrane TNFα‐mediated NF‐κB signaling pathway . It is feasible that the different results are due to the discrepancy of the packaged contents between exosomes derived from DCs and LIPUS‐treated DCs.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted by Gao et al., it was found that mature DC‐derived exosomes could increase endothelial inflammation and atherosclerosis in HUVECs via activation of TNF‐α and the NF‐κB pathway. In the ApoE –/– atherosclerotic mouse model, extended treatment with DC‐derived exosomes led to an increase in atherosclerotic plaques . In one study, researchers investigated exosomes derived from vascular smooth muscle cells, which are involved in the formation of atherosclerotic plaques.…”
Section: Role Of Exosomesmentioning
confidence: 99%
“…Exosomes have an important role in the physiopathological immune response. In vitro and in vivo assays demonstrated that exosomes released by innate immune cells, stromal cells and adaptive immune cells are critical during inflammation by expanding the pro‐inflammatory response, activating other immune cells . Additionally, they have an important role in the progression of the inflammatory response to resolution, immune tolerance and immunomodulation .…”
Section: Granting Tumor Cell Passage By Immunomodulation Of Primary Nmentioning
confidence: 99%